Project-Based Learning on Direct Translation Material with Pop-Up for Students of Walisongo State Islamic University Semarang/التعلّم-القائم على المشاريع لمادة الترجمة الفورية ب” بوب-أب” لدى الطلاب بجامعة والى سونجو الإسلامية الحكومية سمارانج - Husna, Muhammad Ahsanul; Inayah, Inayah; Ismail, Ismail; Salma, Qatrunnada Habibah (ALSUNIYAT: Jurnal Penelitian Bahasa, Sastra, dan Budaya Arab, 2025)
The translation is one of the most essential subjects for foreign speakers. Although there are translation aids for various occasions, translation competence is still a haven for learners. The objectives are to examine Project-Based Learning (Pjbl) for undergraduate students; examine the study planning for the Tarjamah Fauriyyah (TF) material; and the implementation of Pop-Up in TF. This study is qualitative research with an explanatory field study and a cross-sectional survey design. The sample is fifth-year university students in the 2024/2025 academic year, with 14 people. The sampling method was purposive sampling. Data collection, including interviews, observation, and documentation, is analysed using the data reduction model, and conclusions are presented and made. The research findings illustrate that Project-Based-Learning is an active form of student-centred teaching and is implemented on three active learning methods, namely Discovery-Learning, Project-Based-Learning, and Jigsaw, which represent the spirit of the independent curriculum and contribute to the vision of the University. The implication of this research is the implementation of active learning at the university student level by applying the three domains of cognitive, affective, and psychomotor through Pop-Up, which is carried out in groups by students focusing on direct translation learning.